Automation of data acquisition Surface Plasmon Resonance (SPR) based on LabVIEW. (January 2019) - Hendro,; Jerfi,; Viridi, S
Abstract: Evanescent wave is the result of Attenuated Total Reflection (ATR), Surface Plasmon Resonance (SPR) occurs at a specific angle on condition ATR. When a beam is passed through a prism, the beam will experience a reflection on the part of the prism which is in contact with the sample. The result of this reflection to be captured by the detector, On the condition of SPR weaken the intensity of the reflected beam of laser light that occurs because the refracted exponentially away from the boundary of the medium. The LabVIEW-based program has been created that can be used as a tool for experimental SPR, using Motor SHOT 602 and Lock-In Amplifier (SR510). Programs that have been made already equipped with the condition automation starts of movement Motor 2 (Prism), Motor 1 (Detectors), Readings Voltage detectors by Lock-In Amplifier (SR510) and storage of results (time, a position of the motor 1 and 2, the voltage read Lock in Amplifier). Automation program is made by studying the way of the light at Surface Plasmon Resonance (SPR), to determine the relationship between the rotational angle of motor prism and the rotational angle of motor, it can be used for control the position of the sample on the prism and the detector in a program based on LabVIEW.